Quantitative Analysis of a Multiplexed Immunofluorescence Panel in T-Cell Lymphoma. (June 2018) - Ng, Siok-Bian; Fan, Shuangyi; Choo, Shoa-Nian; Hoppe, Michal; Mai Phuong, Hoang; De Mel, Sanjay; Jeyasekharan, Anand D.
Immunohistochemistry (IHC) provides clinically useful information on protein expression in cancer cells. However, quantification of colocalizing signals using conventional IHC and visual scores is challenging. Here we describe the application of quantitative immunofluorescence in angioimmunoblastic T-cell lymphoma (AITL), a peripheral T-cell lymphoma characterized by cellular heterogeneity that impedes IHC interpretation and quantification. A multiplexed immunofluorescence (IF) panel comprising T- and B-lymphocyte markers along with T-follicular helper (TFH ) markers was validated for appropriate cellular localization in sections of benign tonsillar tissue and tested in two samples of AITL, using a Vectra microscope for spectral imaging and InForm software for analysis. We measured the percentage positivity of the TFH markers, BCL6 and PD1, in AITL CD4-positive cells to be approximately 26% and 45%, with 12% coexpressing both markers. The pattern is similar to CD4 cells within the germinal center of normal tonsils and clearly distinct from extragerminal CD4 cells. This study demonstrates the feasibility of automated and quantitative imaging of a multiplexed panel of cellular markers in formalin-fixed, paraffin-embedded tissue sections of a cellularly heterogenous lymphoma. Multiplexed IF allows the simultaneous scoring of markers in malignant and immune cell populations and could potentially increase accuracy for establishment of diagnostic thresholds.